The application of system analysis methods in assessing the quality of bakery products - Ya. V. Maloletkova; S. V. Susarev (Современная наука и инновации)
The food industry is a complex technological system in which automated control is required at every stage. The development of formulations for new functional products entails a number of difficulties associated with controlling the dosage of components and obtaining a product with appropriate quality indicators. Currently, a lot of research is being carried out on adding alternative raw materials to bakery products in order to increase the nutritional value of the final product and give it therapeutic and prophylactic properties. The paper describes the use of systems analysis methods in assessing the quality of bakery products. The assessment of the organoleptic quality indicators of the cake with the addition of Jerusalem artichoke flour was carried out using the Delphi method. The indicators are distributed in order of importance, taking into account the weight coefficient. An example of the final calculation of the score takimg into account the significance coefficient is presented using the example of a cupcake with the addition of 30% Jerusalem artichoke flour. This sample had the best ratings from a group of respondents of different ages, gender and level of education. Based on the results of the study, we can conclude that the use of systems analysis methods in the food industry is necessary to control the quality of products and objectively assess the quality indicators of the final product.